KOOPERACIJA PRIEŠ RINKOS IR VALDŽIOS NESĖKMES, ARBA KAIP ANKSČIAU LAIKO SUKURTI GERĄ KAPITALIZMĄ. - Norkus, Zenonas (Problems / Problemos, 2012)
The paper discusses the role of the cooperation movement in the long-term development of capitalism. This process may end with the perfect capitalism as a complete system of perfectly competitive markets represented in the neoclassical general equilibrium model which is the theoretical source of inspiration for the neoliberal globalist policies. However, real capitalism is imperfect because of numerous market failures. Main causes of these failures are incompleteness and underdevelopment of markets, as well as power and informational asymmetries on the really existing markets. The observation of these imperfections is an inspiration source searching for an alternative and allegedly better socialist economic system. The two main models of socialism are state socialism, which has collapsed because of the massive government failures, and cooperative socialism, which was only partially realized in Communist Yugoslavia and also broke down. However, although the dream about the superior economic alternative to capitalism is an utopia, the consumer, credit and vertical production cooperation between small producers is superior to state capitalism in coping with market failures in the developing countries, interwar Lithuania (1918-1940) being an exemplary case for this statement. The first section of the paper provides the survey of the economic institutions of cooperation in various areas, the second one discusses the ideologies of cooperation movement. Then the comparison of the failures of market, government, and cooperation follows in the third section. Main conclusion is that strong (even if false) ideology can mitigate the failures of cooperation, empowering the cooperation movement helped by the state to correct market failures. In the concluding fourth section this statement is exemplified by the case study of the economic role of the cooperation movement in the interwar Lithuania, where this movement contributed to the building of a distinctive version of the peripheric capitalism -- a state cooperative capitalism.